DEVELOPING NARRATIVE WRITING THROUGH SUSTAINED INSTRUCTION: A LINGUISTIC ANALYSIS OF GRADE 4-6 EFL STUDENTS’ TEXTS - Sitti Maryam (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2026)
Narrative writing is a key genre in upper primary English as a Foreign Language (EFL) education, as it supports learners’ development of extended text construction, genre awareness, and linguistic control. However, many EFL primary students experience difficulties in organizing ideas, sustaining coherence, and using appropriate language features in narrative essays, particularly in exam-oriented contexts. This qualitative classroom-based study investigates the narrative structure and linguistic features of students’ narrative writing produced during a semester-long writing project in an Indonesian primary EFL setting. The study analyzes narrative texts written by Grade 4, Grade 5, and Grade 6 students at Lentera Primary School Makassar, where English is used as the medium of instruction.Adopting a qualitative linguistic approach, the study examines narrative stages (orientation, complication, and resolution), grammatical patterns, vocabulary use, and cohesive devices across grade levels. The findings reveal a clear developmental progression in students’ narrative writing. Grade 4 students predominantly produced linear, event-based texts with limited elaboration and simple sentence structures. Grade 5 students demonstrated improved paragraphing, clearer narrative progression, and greater control of tense and causal relationships. Grade 6 students exhibited the highest level of narrative and linguistic control, including more consistent paragraph organization, increased lexical variety, and the use of complex sentences and reflective resolutions.The findings also indicate that sustained, explicit writing instruction through a semester-long writing project supported students’ ability to respond effectively to essay-based assessment tasks. This study contributes to EFL writing research by providing qualitative linguistic insights into narrative writing development across upper primary grade levels and highlighting the pedagogical value of sustained, genre-based writing instruction in primary EFL classrooms.